O Movimento de Mudança de Sentido Pessoal da Atividade Pedagógica por Professores em Ações de Estudo no Clube de Matemática - Barbosa, Cícero Rodrigues (2025)
Research, as a human activity, seeks to find answers that explain the problems afflicting society and satisfy its needs. Based on this understanding, this research, whose object is the continuing education of teachers who teach mathematics in the early years of primary education, from the perspective of the Teaching Guiding Activity (TGA), aimed to investigate the contributions of the Math Club to the movement of changing the personal meaning of the pedagogical activity for the teacher, given the possibility of organizing teaching from the perspective of TGA. To this end, the methodological approach, based on Historical-Dialectical Materialism, was the formative experiment, based on the Historical-Cultural Theories, the Activity Theory, and the TGA. In order to investigate whether the resignification of the teaching activity aimed at student learning can change the teacher's personal meaning of their pedagogical activity, we sought answers to our research question: How can the Math Club contribute to the movement of changing the teacher's personal meaning of their pedagogical Activity, in the face of the possibility of organizing teaching from the perspective of the TGA? To this end, we started from the premise that the Math Club is a collective space for learning how to teach, as it allows the subjects to understand and experience the process of teaching and learning historically constructed mathematical knowledge, through teaching tasks characterized by playfulness. To answer our research question, we organized a training experiment with math teachers in the early years of primary school in the Goiânia Municipal Education Network, who took part in the course "Clube de Matemática: um espaço coletivo de organização do ensino e da aprendizagem" (Math Club: a collective space for organizing teaching and learning), as an extension project of the Institute for Mathematics and Statistics of the Federal University of Goiás (IME/UFG in Portuguese), in association with the Education Professionals Training Department of the Goiânia Municipal Education Department (Gerfor/SME in Portuguese). The course provided teachers with a training environment that focused on the teaching and learning process of mathematics, grounded in the Historical-Cultural Theories and foundational principles of playfulness and collective work. It was developed in two stages, in the 2023 and 2024 school years, in four modules, with 40 faceto-face meetings and a 240-hour workload, in which we emphasized planning and study actions related to the theoretical-methodological basis of the TGA in the Math Club, collective reflections and evaluation, in addition to the development of Learning Trigger Situations in the club members' schools so that they could experience pedagogical praxis. To understand the totality of the phenomenon in motion, based on the production and apprehension of the data, we created four units of analysis, broken down into six episodes and subdivided into fifteen scenes. Thus, with the concept of pedagogical praxis, we saw the teachers' transformation through the appropriation of theoretical knowledge and the convergence between the social and personal meaning of the pedagogical activity, which allowed them to develop awareness and recognize themselves as subjects of their action. Through the analysis of the data, we proved the thesis that the Math Club, as a collective space for continuing education, based on a movement of change in personal meaning, contributed to the teacher re-signifying their conception of pedagogical activity, given the possibility of organizing math teaching from the perspective of TGA.